Y-STR Haplogroup Diversity in the Jat Population Reveals Several Different Ancient Origins - Mahal, David G.; Matsoukas, Ianis G. (Frontiers in Genetics, 2017)
The Jats represent a large ethnic community that has inhabited the northwest region of India and Pakistan for several thousand years. It is estimated the community has a population of over 123 million people. Many historians and academics have asserted that the Jats are descendants of Aryans, Scythians, or other ancient people that arrived and lived in northern India at one time. Essentially, the specific origin of these people has remained a matter of contention for a long time. This study demonstrated that the origins of Jats can be clarified by identifying their Y-chromosome haplogroups and tracing their genetic markers on the Y-DNA haplogroup tree. A sample of 302 Y-chromosome haplotypes of Jats in India and Pakistan was analyzed. The results showed that the sample population had several different lines of ancestry and emerged from at least nine different geographical regions of the world. It also became evident that the Jats did not have a unique set of genes, but shared an underlying genetic unity with several other ethnic communities in the Indian subcontinent. A startling new assessment of the genetic ancient origins of these people was revealed with DNA science.